Pengaruh Penyemprotan Pupuk Organik Cair Limbah Jeroan Ikan dan Limbah Kulit Nanas Terhadap Laju Pertumbuhan Tanaman Sawi Hijau (Brassica juncea) - Neo Husein Niddai; Agus Suwarni; Rizki Amalia (Poltekkes Kemenkes Yogyakarta, 2020)
Wastes from food industries, such as fish entrails and pineapple peels can raise problems in the corresponding processing because they have organic substance. As an effort to overcome the impacts associated with this two waste types, this study utilize them as liquid organic fertilizer and see its effect to growth rate of green cabbage (Brassica juncea). Therefore, a quasi experiment with pre-test post-test with control group design was conducted. 30 polybag of green cabbage were used as the treatment group and another 30 polybag was treated as the control one, i.e. by using liquid organic fertilizer brand “X”. The plant’s growth rate measured was the changeof weight and the change of leaf number, between the beginning of the study and at 6th week after fertilization. The average weight increase in the treatment group was 211,80 gr, and that in the control group was 210,26 gr. The average leaf addition in the treatment group was 3,46 sheets, meanwhile in the control group it was 3,63 sheets. Towards the weight change, statistical test result by using independent t-test gained a p-value of 0,683; and towards the leaf number change, Mann-Whitney test yielded a p-value of 0,543. So that, it can be concluded that liquid organic fertilizer made of fish entrails and pineapple peels as well as branded “X” liquid organic fertilizer had no different effect on the growrth rate of Brassica juncea.